Synthesis of niobium-doped mcm-48 molecular sieves and its catalytic performance for production of chalcone - Shafizah , Sa'adon (2012)
Mesoporous silica known as M41 S family was discovered as the first ordered mesoporous materials. Among them, MCM-48 a mesoporous cubic system with a highly interwoven and branched pore structure is a potential material in catalyst applications. MCM-48 mesoporous molecular sieves can be conveniently prepared by using rice-husk ash (RHA), an agriculture waste of silica (Si0 2 ) sources. In this research, niobium-doped silica molecular sieves were hydrothermally synthesized utilizing niobiuth ethoxide as the sources of niobium. This niobium species has been introduced into a pure silica MCM-48 without destroying or disturbing its framework structure. The microstructure of mesoporous materials was characterized by a variety of physico-chemical methods such as X-Ray diffraction (XRD), UV-Vis diffuse reflectance, BET Surface Area Analysis, Thermogravimetry Analysis (TGA), Fourier-Transformed Infrared Spectroscopy (FT1R) and Gas Chromatography-Flame Ionized Detector (GC-FID) techniques. Chalcone has been prepared by an aldol condensation between a benzaldehyde and an acetophenone. The percentage of conversion of acetophenone was calculated by using area of peak obtained from GC analysis. The percentage of conversion of the uncalcined MCM-48, calcined MCM-48, 1% Nb-doped MCM-48 and 2% Nb-doped MCM-48 were 21.13%, 27.60%, 34.26% and 39.13% respectively. The niobium-doped MCM-48 has catalyzed the selective chalcone compound and the catalytic activities were ascribed to the strong acidity generated by the presences of the niobium species in MCM-48. It has been proven that the increase in amount of niobium loading in the samples has increased the performance of the catalysts.